High Dose Dexmedetomidine: Effective as a Sole Agent Sedation for Children Undergoing MRI - Sheikh Sohail Ahmed; Tamara Unland; James E. Slaven; Mara E. Nitu (International Journal of Pediatrics)
Objective. To determine the efficacy and safety of high dose dexmedetomidine as a sole sedative agent for MRI. We report our institution’s experience. Design. A retrospective institutional review of dexmedetomidine usage for pediatric MRI over 5.5 years. Protocol included a dexmedetomidine bolus of 2 μg/kg intravenously over ten minutes followed by 1 μg/kg/hr infusion. 544 patients received high dose dexmedetomidine for MRI. A second bolus was used in 103 (18.9%) patients. 117 (21.5%) required additional medications. Efficacy, side effects, and use of additional medicines to complete the MRI were reviewed. Data was analyzed using Student’s t-test, Fisher’s exact test, and Analysis of Variance (ANOVA). Main Results. Dexmedetomidine infusion was associated with bradycardia (3.9%) and hypotension (18.4%). None of the patients required any intervention. Vital signs were not significantly different among the subgroup of patients receiving one or two boluses of dexmedetomidine or additional medications. Procedure time was significantly shorter in the group receiving only one dexmedetomidine bolus and increased with second bolus or additional medications (P<0.0001). Discharge time was longer for children experiencing bradycardia (P=0.0012). Conclusion. High dose Dexmedetomidine was effective in 78.5% of cases; 21.5% of patients required additional medications. Side effects occurred in approximately 25% of cases, resolving spontaneously.